2012
DOI: 10.1016/j.clnu.2012.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive period in flavor learning: Effects of duration of exposure to formula flavors on food likes during infancy

Abstract: Background & Aims Emerging research has revealed the existence of periods in which the developing brain has heightened sensitivity to environmental influences. We discovered a sensitive period, <4 months of age, when exposure to the flavor of extensively hydrolyzed protein hydrolysate formulas (ePHF) determines its hedonic tone. This formula has pronounced bitter, sour, and savory tastes compared to cow-milk-based formulas (CMF). This study aimed to determine the effects of duration of exposure during the sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 17 publications
2
45
0
4
Order By: Relevance
“…Knowledge about the sensitive periods for learning about flavors that are not associated with the maternal diet (19,29) and for other senses, particularly vision (44), may shed light on aspects of flavor learning that have not been explored. Most likely, there are multiple sensitive periods especially because learning about flavors and foods does not end with breastfeeding but continues throughout complementary feedings (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge about the sensitive periods for learning about flavors that are not associated with the maternal diet (19,29) and for other senses, particularly vision (44), may shed light on aspects of flavor learning that have not been explored. Most likely, there are multiple sensitive periods especially because learning about flavors and foods does not end with breastfeeding but continues throughout complementary feedings (13).…”
Section: Discussionmentioning
confidence: 99%
“…One challenge in investigating how children learn to like healthy foods such as vegetables is to determine whether there are optimum times when an experience promotes greater liking (19). A previous trial showed a greater liking of carrot-flavored cereal by infants whose lactating mothers were randomly assigned, during the first 3.5 postpartum months, to drink carrot juice, which flavored their breast milk (20), compared with avoiding carrot juice and drinking water (16).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ePHF-fed as well as breastfed infants were more likely to display positive facial reactions to savory-tasting cereal, perhaps because breast milk [55] and ePHF [56] are both high in the savory amino acid glutamate. Other research has shown that the length of time infants are fed ePHF influences their responses to savory food; those fed ePHF for at least 3 months showed greater acceptance of a savory broth relative to a plain broth [57] . Evidence shows that these early preferences can be long-lasting.…”
Section: Formulamentioning
confidence: 99%
“…Effects of experience with foods and fluids both pre-and post-natally on later food preferences are seen in children as well (e.g. Mennella, 2014;Mennella & Castor, 2012;Mennella, Jagnow, & Beauchamp, 2001), with childhood functioning as a time during which information about how sweet foods are "supposed" to taste is acquired (e.g. Beauchamp & Cowart, 1985;Birch & Anzman-Frasca, 2011).…”
Section: Exposure and Experiencementioning
confidence: 99%
“…Mennella & Castor, 2012). From very early in life, sweet tastes elicit behavioral responses suggesting they are highly pleasant, and newborns of many mammalian species display strong preferences for sweet tastes relative to water (for review, see Mennella, 2014).…”
Section: Obesity Sugary Drinks and Diseasementioning
confidence: 99%